Inquiry-Based Learning in History Teacher Education: A Local History Approach to Prospective Teachers’ Understanding - Arif Saefudin; Johan Wahyudhi; Yusran Ilyas; Loso Judijanto; Akhlaqur Rahman (Sakura Digital Nusantara, 2026)
Purpose: Traditional history teaching methods in the social sciences often overlook constructivist and inquiry-based approaches, meaning that trainee history teachers are under-exposed to such approaches. This study aims to evaluate how trainee history teachers understand and apply inquiry-based methods when local history is integrated into teaching materials, as well as to assess the pedagogical effectiveness of local history in enhancing teacher education. Methods: This study employed an exploratory qualitative approach involving history teacher trainees enrolled in a teacher training programme at UIN Syarif Hidayatullah Jakarta. Data were collected through focus group discussions, interviews, and classroom-based inquiry activities. Data were analysed using thematic analysis to identify patterns in participants’ understanding and perceptions of inquiry-based learning utilising local history. Findings: The findings indicate that integrating local history into the curriculum significantly enhances participants’ engagement and interest. Students demonstrated a deeper understanding of inquiry-based learning, particularly in formulating questions, analysing sources, and drawing evidence-based conclusions. Participants also reported increased confidence in applying inquiry-oriented teaching methods, although concerns regarding classroom implementation remain. Research implications: This study is limited to specific groups and contexts, which may affect generalisability. However, it highlights the pedagogical value of contextual and inquiry-based approaches in teacher education. Challenges such as time constraints and institutional readiness need to be considered for wider implementation. Originality: This research contributes by demonstrating the effectiveness of local history as a pedagogical medium to support inquiry-based learning. It offers a contextual approach to bridging theory and practice in teacher education and suggests directions for future longitudinal research on sustained pedagogical impacts.